Advantage of Backwardness: The Effect of Industrialisation on European Modern Design Movement - Wang, Zhiyong (European Scientific Journal, ESJ, 2023)
To answer specific questions of modern design history, historical analysis is needed, alongside chronicles and narrative, to promote deeper understanding. This paper, with the assistance of advantage of backwardness theory and the method characterised by historical sociology, focuses on the social origin of European modern design against the background of the industrial revolution. It aims to understand the link between technological change and the rise of modern design in Europe. The study starts with an explanation of the progress of industrialisation within those countries that were closely related to European modern design movement, and then investigates how this process diversely impacted the emergence of modern design in Europe through a comparative analysis on the interactive connection between industrialisation (as a case of technological change in modern times) and European modern design movement (as a cultural and social consequence of the change). This study particularly clarifies why the subsequent industrial countries, instead of the early industrial countries, had dramatically obtained the advantage to fully develop the modern design movement in Europe. It concludes that, in terms of technological change, advantage of backwardness played an important part in the origin of European modern design.